2012
DOI: 10.1134/s0040579512030013
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of pomegranate seed oil using subcritical propane and supercritical carbon dioxide

Abstract: Extraction of oil from pomegranate seeds as a waste product of the juice industry using supercrit ical carbon dioxide and subcritical propane was studied in this work. The influence of the main operating con ditions of extraction, namely, the temperature and pressure of extraction on the oil extraction yield and the correspondent fatty acid profile were analyzed and reported here. Soxhlet extraction with n-hexane was done for comparison with supercritical extraction resulting in a maximum yield of oil of 22.31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 20 publications
3
35
1
1
Order By: Relevance
“…This technology is considered to be clean because, at the end of the extraction, the solvent is completely removed by system depressurization and can be recovered. Although carbon dioxide is the most commonly used fluid in this kind of extraction, subcritical propane allows high extraction rates when used in processes with vegetable oil [7][8][9][10][11] due to the greater solubility of the triglycerides in this solvent [12]. In addition, it can be used at lower pressures, which is an important advantage in the oil extraction industry.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is considered to be clean because, at the end of the extraction, the solvent is completely removed by system depressurization and can be recovered. Although carbon dioxide is the most commonly used fluid in this kind of extraction, subcritical propane allows high extraction rates when used in processes with vegetable oil [7][8][9][10][11] due to the greater solubility of the triglycerides in this solvent [12]. In addition, it can be used at lower pressures, which is an important advantage in the oil extraction industry.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine, Raphanus sativus seed oil, which is rich in sulforaphene, is used to improve intestinal function and for treatment of digestive problems [4]. Studies have shown that oil yields from Raphanus sativus seeds can be as high as 35-40 %, making them potential new oil sources for food, medicine and cosmetic industries [5].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine, radish seed oil, which is rich in sulforaphene is used to improve intestinal function and for treatment of digestive problems [4]. Studies have shown that oil yields from radish seeds can be as high as 35-40 %, making them potential new oil sources for food, medicine and cosmetic industries [5].…”
Section: Introductionmentioning
confidence: 99%